National action plans to tackle NCDs: role of stakeholder network analysis. (20th May 2019) - Hunter, Ruth F; Wickramasinghe, Kremlin; Ergüder, Toker; Bolat, Abdulkadir; Arı, Hakan Oğuz; Yıldırım, Hasan Hüseyin; Ursu, Pavel; Robinson, Gareth; Breda, Joao; Mikkelsen, Bente; Connolly, Paul; Clarke, Mike; et al.
Abstract : Network science approaches can enhance global and national coordinated efforts to prevent and manage non-communicable diseases, say Ruth Hunter and colleagues